Awareness, Attitude and Practice of keeping proper oral hygiene among the Medical and Dental students - Muhammad Adnan Iqbal, Sadia Rashid, Muhammad Rizwan, Wajahat Ghafoor Ch, Qaiser Masud Sheikh, Asif Noor (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the perspective of awareness, attitude and practice of keeping good oral hygiene among the Medical and dental college students of Islamabad and Abbottabad. Methods: This comparative cross-sectional questionnaire-based study was conducted in HBS and Federal Medical and Dental College Islamabad and Frontier Medical and Dental College Abbottabad from July to December 2021. A sample of 900 medical and dental students of 1st, 2nd and 3rd year MBBS and BDS, 300 from each college were selected randomly. Result: Number of Female students was more than male students with an age range between 17-22 years in all three colleges. Majority of the students had insufficient awareness and knowledge about various available dental hygiene aids, their proper usage and impact on health status. Good practice, knowledge and attitude of dental hygiene was shown by less than 50% of students, majority students of Islamabad than Abbottabad. Conclusion: Average level of AAP about oral hygiene was seen among the Medical and Dental students of all colleges. Organizing various counseling sessions, community work and seminars to highlight the importance of oral hygiene, various tools available and their proper usage was suggested.